2008
DOI: 10.1074/jbc.m805258200
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Coactivators SAGA, SWI/SNF, and Mediator Make Distinct Contributions to Activation of Glucose-repressed Genes

Abstract: The paradigm of activation via ordered recruitment has evolved into a complicated picture as the influence of coactivators and chromatin structures on gene regulation becomes understood. We present here a comprehensive study of many elements of activation of ADH2 and FBP1, two glucose-regulated genes. We identify SWI/SNF as the major chromatin-remodeling complex at these genes, whereas SAGA (Spt-AdaGcn5-acetyltransferase complex) is required for stable recruitment of other coactivators. Mediator plays a crucia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 49 publications
3
46
0
1
Order By: Relevance
“…Hyperacetylated histones promote recruitment of SWI/SNF in vitro (Hassan et al 2002), consistent with the requirement for both Gcn5, the HAT subunit in SAGA, and Snf2 for nucleosome remodeling at ADH2 (Verdone et al 2002;Biddick et al 2008) and PHO8 (Gregory et al 1999). Gcn5 and Snf2 also promote remodeling at PHO5 under suboptimal induction conditions (Barbaric et al 2007), although Pho4 binding at PHO5 is impaired in snf2Δ and gcn5Δ cells under certain conditions (Adkins et al 2007).…”
supporting
confidence: 64%
“…Hyperacetylated histones promote recruitment of SWI/SNF in vitro (Hassan et al 2002), consistent with the requirement for both Gcn5, the HAT subunit in SAGA, and Snf2 for nucleosome remodeling at ADH2 (Verdone et al 2002;Biddick et al 2008) and PHO8 (Gregory et al 1999). Gcn5 and Snf2 also promote remodeling at PHO5 under suboptimal induction conditions (Barbaric et al 2007), although Pho4 binding at PHO5 is impaired in snf2Δ and gcn5Δ cells under certain conditions (Adkins et al 2007).…”
supporting
confidence: 64%
“…Although we found that Mediator occupies the CYC1 promoter only after activation, the Mediator complex has a well-established role in RNAPII recruitment (Biddick et al 2008;Esnault et al 2008). To rule out the possibility that Mediator influences recruitment of RNAPII to the CYC1 promoter, chromatin immunoprecipitation of RNAPII was performed in the med18D and med19D strains.…”
Section: Resultsmentioning
confidence: 89%
“…Relief from glucose repression (derepression) is accompanied by promoter binding of Adr1 in a Snf1-dependent fashion (31) and requires Snf1-dependent histone H3 hyperacetylation of promoter nucleosomes (20,32). Chromatin remodeling precedes and is required for gene activation and requires Snf1, Adr1, and Cat8, which recruit the Swi/Snf chromatin remodeling complex as well as the SAGA (Spt-Ada-Gcn5 acetyltransferase), and NuA4 histone acetyltransferase complexes (33,34). Impaired histone deacetylase activity or deletion of the histone H3 or histone H4 tail allows Adr1 binding and preinitiation complex (PIC) formation in the presence of glucose (32,35,36).…”
mentioning
confidence: 99%